Letter - Haldane, Charlotte Franken, 1894-1969
034-0115-001 INTERNATIONAL BRIGADE Dependants and Wounded Aid Committee Patrons: Harry Adams The Duchess of Atholl, MP. H.N. Brailsford Seymour Cocks, MP Ebby Edwards Prof. J.B.S. Haldane. F.R.S. Oliver Harris Will Lawther Sir Walter Layton Earl of Listowel Sir Peter Chalmers Mitchell, C.B.E.. F.R.S., F.Z.S.. D.Sc LL.D. J.B. Priestley Eleanor Rathbone, M.P. Ald. J. Reeves E. Shinwell, M.P. W.J.R. Squance G.R. Strauss, M.P. Wilfrid Roberts, M.P. Ellen Wilkinson. M.P. Hon Secretary: CHARLOTTE HALDANE Telephone: Temple Bar 0178 1 LITCHFIELD STREET, LONDON, W.C.2. December 6th, 1938. Mr. Tewson, Transport House, Smith Square, S.W.1. Dear Mr.Tewson, The men of the British Battalion of the International Brigade will arrive home from Spain tomorrow evening, Wednesday, drawing in at Victoria Station by the 6.45 train. We extend a cordial invitation to you to be present at the platform reception which will be given to those men. I am enclosing two passes, one which will get you to the platform, and one which will take you past the barrier where the Brigade men will be assembled. We are sure the men of the International Brigade would deeply welcome your presence it this reception on the platform. Yours sincerely Charlotte Haldane (Hon Secretary). P.S. A dinner is being held in honour of the men, which will be presided over by Mr. Wilfrid Roberts, M.P. It will be held in the C.W.S. Assembly Rooms, Leman St, Stepney, at 8.15 p.m. on Wednesday, and you are cordially invited to attend, for which a pass is enclosed. 292/946/34/115